Nasionalisme Soekarno Perspektif Pendidikan Islam - Eliyanto '; Siti Saudah (LPPM IAINU Kebumen, 2019)
Soekarno's thoughts on nationalism received much opposition from various groups in the Islamic community, because they were considered contrary to Islamic teachings and divided the people. This assumption is of course unfounded because it only judges from the understanding of Nationalism in general. While Islamic education itself assesses Sukarno's nationalism in accordance with the goals and direction of Islamic education. Soekarno's nationalism substance leads to liberation, patriotism, humanity, pluralism, democratization and unity. Soekarno's nationalism with its various forms of implication, namely patriotism, unity and unity, love for the motherland and nation, pluralism, humanism and compassion, liberation, has a value of relevance to the existence of Islamic education, both in terms of the goals of Islamic education and its scope.